2015
DOI: 10.3390/ijerph121013053
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Particulate Air Pollution Associated with Increased Risk of Hospital Admissions for Respiratory Diseases in a Tropical City, Kaohsiung, Taiwan

Abstract: This study was undertaken to determine whether there was an association between coarse particles (PM2.5–10) levels and frequency of hospital admissions for respiratory diseases (RD) in Kaohsiung, Taiwan. Hospital admissions for RD including chronic obstructive pulmonary disease (COPD), asthma, and pneumonia, and ambient air pollution data levels for Kaohsiung were obtained for the period from 2006 to 2010. The relative risk of hospital admissions for RD was estimated using a case-crossover approach, controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 72 publications
4
44
1
1
Order By: Relevance
“…Other studies have shown the significant effect of increased ambient NO 2 with hospital admissions due to COPD or asthma in Shiraz, Iran; 51 the Netherlands, 20 and Italy. 52 In Taiwan, increase in PM 2.5 and PM 10 , increased hospital admissions for COPD, asthma, and pneumonia; 19,53 and in Italy increase in PM 10 , increased the risk of hospitalization due to COPD in the whole year, and this effect was stronger in the warm season. 52 A review estimated that each 10 μg/m 3 increase in PM 2.5 , NO 2 and SO 2 was associated with a 2.5%, 4.2%, and 1.2% increase in hospital admissions and COPD emergencies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown the significant effect of increased ambient NO 2 with hospital admissions due to COPD or asthma in Shiraz, Iran; 51 the Netherlands, 20 and Italy. 52 In Taiwan, increase in PM 2.5 and PM 10 , increased hospital admissions for COPD, asthma, and pneumonia; 19,53 and in Italy increase in PM 10 , increased the risk of hospitalization due to COPD in the whole year, and this effect was stronger in the warm season. 52 A review estimated that each 10 μg/m 3 increase in PM 2.5 , NO 2 and SO 2 was associated with a 2.5%, 4.2%, and 1.2% increase in hospital admissions and COPD emergencies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The effects of air pollution on the respiratory system include increased respiratory symptoms, decreased lung function, and increased incidence of chronic cough and bronchitis. 8,9 Epidemiological and clinical studies show that in children and adults, increased hospital admissions, lung diseases, lung cancer, 10 bronchiectasis, [11][12][13][14] respiratory infection, pulmonary embolism, asthma, 2,6,[15][16][17][18] and chronic obstructive pulmonary diseases (COPD) 9,[19][20][21][22][23] are affected by air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis A time -series regression analysis [10][11][12] was used to examine the association between short -term fluctuations in air pollutants (PM 2.5 , PM 10 , NO 2 ) and hospital admissions for MI, using a generalized linear model and distributed lag model with the Poisson distribution. We used a previously verified generalized linear model to evaluate the relationship between air pollutants and hospital admissions, with the number of hospital admissions as the dependent variable 10-12 and the daily mean level of each individual air pollutant as the main exposure variable.…”
mentioning
confidence: 99%
“…Respiratory health effects have been reported due to both short-term exposure (17,27,28) and to long-term exposure of air pollution (26,29,30). Among the air pollutants, particulate matter has received special attention as they are considered as a major component causing adverse health effects (18,22,(31)(32)(33)(34)(35)(36)(37)(38)(39). The effects of other air pollutants such as ozone (O3), nitrogen oxides (NO2, NOx), sulphur dioxide (SO2) and carbon monoxide (CO) on health have been also examined in recent studies (8,10,13,18,40,41).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…and PM1, and response was examined up to three days prior to the hospital admissions (0-3 days) as this is the most common period found to be significant in most previous studies (33,(247)(248)(249). The effect of temperature on the same day as the outcome event was controlled as a confounding factor in all models (250).…”
Section: Statistical Analysesmentioning
confidence: 99%